PENDAMPINGAN PENYUSUNAN TUNTUNAN TAHLIL BERBASIS DIGITAL DAN NON-DIGITAL MAKAM WALIULLAH SIMBAH BUYUT NDUKOH SEBAGAI UPAYA PENGUATAN SPIRITUALITAS DI TENGGER WETAN - Nur Afifah Rindiani; Ulya Ainur Rofiah; Siti Zulaikhah; Putri Wijayanti; A. Rolly Akmal Abdillah; Muamar Kadhafi (CV. Kalimasada Group, 2026)
The mentoring program for developing digital and non-digital Tahlil guidelines at the tomb of Waliullah Simbah Buyut Ndukoh, Tengger Wetan, represents a community service initiative conducted by KKN students of IAINU Tuban, focusing on strengthening spirituality and preserving local cultural values. This study aims to examine the process and outcomes of community assistance using the Asset-Based Community Development (ABCD) approach in optimizing local community assets. The method employed is participatory, involving social mapping, group discussions, and collaboration with religious leaders, tomb caretakers, youth organizations, and local religious groups. The findings indicate that the tradition of tahlil and pilgrimage functions not only as a religious practice but also as a collective identity and a source of social cohesion within the community. The program resulted in the development of contextual, educational, and technology-adaptive Tahlil guideline books in both printed and digital formats. Furthermore, the initiative contributed to enhancing religious literacy, strengthening intergenerational knowledge transmission, and fostering active community participation in preserving spiritual traditions. Therefore, the ABCD approach proves to be effective in establishing a sustainable community empowerment model through the integration of local wisdom and digital innovation.